Differences in Physical Activity, Physical Function, and Diet Intake, in Men and Women Living With HIV in the United States: A Cross-Sectional Study - Webel, Allison R.; Dos Santos, Andre Pereira; Davey, Christine Horvat; Oliveira, Vitor; Cleveland, David; Buford, Thomas W.; Burkholder, Greer; Crane, Heidi M.; Fleming, Julia; Willig, Amanda L. (The Journal of the Association of Nurses in AIDS Care, 2025)
Our study aimed to characterize physical activity, diet quality, and physical function among people with HIV (PWH) and to assess differences by sex. A total of 706 PWH completed measurements of physical activity (actigraphy accelerometers), diet quality (24-hr recalls), handgrip strength, and physical function (Short Physical Performance Battery). Most participants were male, Black, and employed. Less than half met physical activity guidelines, with more men meeting recommendations than women (45% vs. 28%, p < .001). Men also consumed more calories, protein, fiber, and iron than women (all p < .001). Only 10% of participants met physical activity and diet recommendations, with nearly twice as many men as women achieving both. PWH exhibited low physical activity and poor diet quality, particularly among women. Promoting optimal lifestyle behaviors is critical as PWH age and improve their health span.